Abicht and Śniadecki: about a Turbulent Philosophical Dispute at the Imperial University of Vilnius in 19th century - Kupś, Tomasz (Problemos, 2023)
The article presents the results of source research conducted on the scholarly and teaching activities of the German philosopher and educator Johann Heinrich Abicht (1762–1816) who in 1804 was employed at the Imperial University of Vilnius. Research in Lithuanian, Polish, Ukrainian, and German archives has revealed many facts about Abicht’s scholarly and teaching activities in Vilnius, most of which fall during the period when Jan Śniadecki (1756–1830) was Rector at the Imperial University of Vilnius. In this paper I argue that it was Abicht and his Vilnius-based scholarly and teaching activities that were the direct cause of Śniadecki’s publication of the essay On Metaphysics in 1814, and indirectly also the trigger for all of Śniadecki’s later philosophical writings.